Neutron Backscattering Technique for the Detection of Buried Organic Objects (2009)
Abstract. The subject of the present work is to study through a Monte Carlo simulation (Geant4) and experimentally, the neutron backscattering technique for the detection of hydrogen-rich materials. This technique is based on the efficiency of these kind of materials to thermalize fast neutrons. The number of backscattered low energy, or thermal, neutrons is a direct indication of the presence of an hydrogen-rich objects. It was studied the influence of several geometrical parameters and in particular the influence of the moisture content on the technique response. The effect that produces the moisture in the range 0-10% by weight (an increment in the amplitude of the signal) had not been seen previously in related works. This effect was interpreted and checked by means of simulations and a theoretical approximation as an effect of pre-thermalización, where the moisture in this range of homogeneous values ¨helps¨ to the detection of the object. Extrapolating the results obtained experimentally to soils with a larger saturation moisture (related to the capacity of water retention) and supported on the realized simulations, there were obtained results that describe the possibility of detecting the buried object to high moisture values looking for inverse signals (negative values of the relative amplitude).